Public services exemptions in EU free trade and investment agreements - Krajewski, Markus (T.M.C. Asser Press, 2015)
This chapter analyses the various approaches used in free trade agreements to safeguard regulatory space for the provision, financing and organisation of public services. It focuses on agreements signed by the EU including texts of recently negotiated agreements and drafts of agreements under negotiation. After a brief overview of the current state-of-affairs of existing free trade agreements of the EU and of current negotiations the chapter explains why the obligations of free trade agreements may potentially conflict with the special function of the provision and organisation of public services. The main part of the chapter is devoted to the development and explanation of an analytical framework concerning the various exemptions and clauses which allows an assessment of the impact of a particular free trade agreement independently of a specific existing model. Based on this analytical framework, the current approach of the EU regarding public service exemptions in free trade agreements is assessed. The chapter concludes with some reform proposals.
CRIS-Team Scopus Importer:2023-03-21